2012
DOI: 10.1371/journal.pgen.1003077
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Genome Instability and Preneoplastic Processes through Loss of Fhit Expression

Abstract: Genomic instability drives tumorigenesis, but how it is initiated in sporadic neoplasias is unknown. In early preneoplasias, alterations at chromosome fragile sites arise due to DNA replication stress. A frequent, perhaps earliest, genetic alteration in preneoplasias is deletion within the fragile FRA3B/FHIT locus, leading to loss of Fhit protein expression. Because common chromosome fragile sites are exquisitely sensitive to replication stress, it has been proposed that their clonal alterations in cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(164 citation statements)
references
References 68 publications
4
157
0
3
Order By: Relevance
“…Similar results highlight the contribution of the FHIT gene, which encompasses FRA3B and encodes a 14-kDa protein with tumor suppressor functions (55). Deficiency of the FHIT gene as early as in preneoplastic lesions induced global genome instability and clonal expansion (56,57). Likewise, the product of FRA15A (RORA) and FRA8I (SPIDR), which is inactivated in multiple tumors, has been shown to be involved in cellular stress response, DNA damage repair, and maintenance of chromosomal integrity (58,59), suggesting that their impaired activity may contribute to genomic instability in cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…Similar results highlight the contribution of the FHIT gene, which encompasses FRA3B and encodes a 14-kDa protein with tumor suppressor functions (55). Deficiency of the FHIT gene as early as in preneoplastic lesions induced global genome instability and clonal expansion (56,57). Likewise, the product of FRA15A (RORA) and FRA8I (SPIDR), which is inactivated in multiple tumors, has been shown to be involved in cellular stress response, DNA damage repair, and maintenance of chromosomal integrity (58,59), suggesting that their impaired activity may contribute to genomic instability in cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…We employed Fhit − / − mice because of their sensitivity to carcinogen induction of various tumor types, and B6 mice as wt control cohort. We have previously reported that Fhit deficiency causes genome instability that is undetected by cellular checkpoints 24, providing an optimal environment for selection and clonal expansion to survive various stressors 25. For instance, we have shown that Fhit − / − mouse kidney cells survive acute DMBA treatment and chronic severe nutritional stress whereas wt cells do not 25.…”
Section: Discussionmentioning
confidence: 99%
“…Also, loss of expression of Fhit tumor suppressor protein occurs in >50% of human cancers 23. Fhit also serves as a genome caretaker preventing the onset of global genome instability 24, 25. Fhit‐deficient and haploinsufficient mice spontaneously develop lung tumors, lymphomas and liver hemangiomas at slightly higher incidences than wt mice 21 and 100% of Fhit knockout mice developed NMBA‐induced forestomach tumors, significantly more than wt mice 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…Replication stress and A3-induced mutagenesis have recently been linked to loss of a chromosomal fragile site gene, FHIT [63]. FHIT is frequently lost very early in tumor development, causing replication stress due to deoxythymidine triphoshate (dTTP) depletion [64]. When genomic sequences from lung adenocarcinomas were stratified by A3B and FHIT expression, those with high A3B and FHIT loss showed significantly higher A3 signature mutation loads than high A3B expressers with normal FHIT levels, thus the mutagenic potential of A3B may be unleashed in the absence of FHIT [63].…”
Section: Availability Of Ssdna Substratementioning
confidence: 99%